Guest Editorial: The Nexus of Violence, Violence Research, and Development. Introduction to the Focus Section - Imbusch, Peter; Veit, Alex (International Journal of Conflict and Violence (IJCV), 2011)
This focus section of the International Journal of Conflict and Violence is dedicated to violence and violence research in the Global South. It examines the causes, forms, perpetrators, processes, and outcomes of violence. While the contributions go into detail on what is commonly understood as politically motivated violence, they also examine societal, criminal, urban, and gendered violence, as well as the involvement of youth. Four articles explore the significance of violence in specific regions: Africa south of the Sahara, West Asia and North Africa, East Asia, and Latin America and the Caribbean. The authors describe and assess the state of research within and about the different countries. Two further articles review the body of research on the causes of civil war, which has been the dominant issue in much violence-related research on the global South since the end of the Cold War.